Gut microbiota depletion minimally affects the daily voluntary wheel running activity and food anticipatory activity in female and male C57BL/6J mice - Ehichioya, David E.; Taufique, S. K. Tahajjul; Magaña, Isabel; Farah, Sofia; Obata, Yuuki; Yamazaki, Shin (Frontiers in Physiology, 2023)
Emerging evidence has highlighted that the gut microbiota plays a critical role in the regulation of various aspects of mammalian physiology and behavior, including circadian rhythms. Circadian rhythms are fundamental behavioral and physiological processes that are governed by circadian pacemakers in the brain. Since mice are nocturnal, voluntary wheel running activity mostly occurs at night. This nocturnal wheel-running activity is driven by the primary circadian pacemaker located in the suprachiasmatic nucleus (SCN). Food anticipatory activity (FAA) is the increased bout of locomotor activity that precedes the scheduled short duration of a daily meal. FAA is controlled by the food-entrainable oscillator (FEO) located outside of the SCN. Several studies have shown that germ-free mice and mice with gut microbiota depletion altered those circadian behavioral rhythms. Therefore, this study was designed to test if the gut microbiota is involved in voluntary wheel running activity and FAA expression. To deplete gut microbiota, C57BL/6J wildtype mice were administered an antibiotic cocktail via their drinking water throughout the experiment. The effect of antibiotic cocktail treatment on wheel running activity rhythm in both female and male mice was not detectable with the sample size in our current study. Then mice were exposed to timed restricted feeding during the day. Both female and male mice treated with antibiotics exhibited normal FAA which was comparable with the FAA observed in the control group. Those results strongly suggest that gut microbiota depletion has minimum effect on both circadian behavioral rhythms controlled by the SCN and FEO respectively. Our result contradicts recently published studies that reported significantly higher FAA levels in germ-free mice compared to their control counterparts and gut microbiota depletion significantly reduced voluntary activity by 50%.